вправа 3.11 гдз 11 клас математика Нелін Долгова 2019

 
Вправа 3.11


Умова:
 
 
Знайдіть:
1) log89, якщо log1218 = a;
2) log915, якщо log4525 = a.


Відповідь ГДЗ:

1) Перетворимо: \begin{equation} log_{12}18=\frac{log_{3}18}{log_{3}12}= \end{equation} \begin{equation} =\frac{log_{3}9+log_{3}2}{log_{3}3+log_{3}4}= \end{equation} \begin{equation} =\frac{2+log_{3}2}{1+2log_{3}2} \end{equation} За умовою log1218 = a, тоді \begin{equation} \frac{2+log_{3}2}{1+2log_{3}2}=a \end{equation} 2 + log32 = a(1 + 2log32)
2 + log32 = a + 2alog32
2alog32 - log32 = 2 - a
(2a - 1)log32 = 2 - a \begin{equation} log_{3}2=\frac{2-a}{2a-1} \end{equation} Також перетворимо log89: \begin{equation} log_{8}9=log_{2}^{3}3^{2}=\frac{2}{3}log_{2}3= \end{equation} \begin{equation} =\frac{2}{3}\cdot \frac{1}{log_{3}2}= \end{equation} \begin{equation} =\frac{2}{3}\cdot \frac{2a-1}{2-a}= \end{equation} \begin{equation} =\frac{2(2a-1)}{3(2-a)}. \end{equation} Відповідь: \begin{equation} \frac{2(2a-1)}{3(2-a)} \end{equation} 2) log915 - ? \begin{equation} log_{45}25=\frac{log_{5}25}{log_{5}45}= \end{equation} \begin{equation} =\frac{log_{5}5^{2}}{log_{5}5\cdot 9}= \end{equation} \begin{equation} =\frac{2log_{5}5}{log_{5}57log_{5}9}= \end{equation} \begin{equation} =\frac{2}{1+log_{5}9}= \end{equation} \begin{equation} =\frac{2}{1+2log_{5}3} \end{equation} За умовою log4525 = a, тоді: \begin{equation} \frac{2}{1+2log_{5}3}=a \end{equation} \begin{equation} 1+2log_{5}3=\frac{2}{a} \end{equation} \begin{equation} 2log_{5}3=\frac{2}{a}-1 \end{equation} \begin{equation} log_{5}3=\frac{1}{a}-\frac{1}{2} \end{equation} \begin{equation} log_{5}3=\frac{2-a}{2a} \end{equation} \begin{equation} log_{5}3=\frac{2a}{2-a} \end{equation} Перетворимо log915: \begin{equation} log_{9}15=log_{3}^{2}5\cdot 3= \end{equation} \begin{equation} =\frac{1}{2}log_{3}5\cdot 3= \end{equation} \begin{equation} =\frac{1}{2}(log_{3}5+log_{3}3)= \end{equation} \begin{equation} =\frac{1}{2}(log_{3}5+1)= \end{equation} \begin{equation} =\frac{1}{2}(\frac{2a}{2-a}+1)= \end{equation} \begin{equation} =\frac{1}{2}\cdot \frac{2a+2-a}{2-a}= \end{equation} \begin{equation} =\frac{a+2}{2(2-a)}. \end{equation} Відповідь: \begin{equation} \frac{a+2}{2(2-a)} \end{equation}

реклама